Manufacturing of Cf/SiC Composites through Combined CVI and High-Pressure PIP Process - Won Im, Dong; Kim, Tae-Eon; Chul Bae, Jin; Yeon Cho, Kwang; Sup Lim, Jung; Il Kim, Jung (Asian Journal of Chemistry, 2014)
Carbon fiber-reinforced SiC matrix (Cf/SiC) composites were fabricated using a chemical vapor infiltration + polymer infiltration and pyrolysis (CVI+PIP) hybrid process. In an effort to improve the yield of SiC pyrolyzed during PIP, we conducted pyrolysis under high pressure using polycarbosilane as a precursor. We investigated the effects of the high-pressure pyrolysis of the polycarbosilane infiltrate on the efficiency of the PIP process and the physical characteristics of the fabricated Cf/SiC composites. The CVI+PIP hybrid process under high-pressure pyrolysis reduced the processing time by a factor of ten, minimized the oxygen content (< 10 at %) and improved the crystallinity of the nano b-SiC crystal. These results are due to the pressure in the polycarbosilane pyrolysis, which resulted in a high polycondensation. The ceramic yield of polycarbosilane infiltrated into Cf-preform was increased and the inter-facial bonding between the matrix and fibers was improved. Consequently, the Cf/SiC composites fabricated by the CVI+PIP hybrid process under high-pressure pyrolysis exhibited a high density of 2.15 g/cm3.